PENGARUH STRATEGI DRTA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA DAN LITERASI SISWA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS V MIS ALKHAIRAT DELITUA TAHUN AJARAN 2016/2017 - hasni suciwati (Komunikologi: Jurnal Pengembangan Ilmu Komunikasi dan Sosial, 2018)
This study aims to determine the implementation of learning, reading ability of students, and the influence of DRTA strategy on the ability to read students' understanding on the subjects of Indonesian language in class Five Elementary School MIS Alkhairat Delitua Academic Year 2016/2017. The method used in this research is Quasi Eksperimen with pretest and posttest research design.This research was conducted at MIS Alkhairat Delitua, Academic Year 2016/2017. The population of this study is all students of grade Five MIS Alkhairat Delitua which amounted to 54 students. The sample of this research is Class Five-A as experiment class with the number of 28 students and class Five-B as control class with the number of 26 students. The data collection tool in this research is teacher and student observation sheet and essay test as many as 5 questions. before the two classes were given different treatment, the first two classes were given pretest questions to know the students' initial ability.So it can result the average score of Five-A students is 50.03 and the average grade of Five-B students is 47.30. After the two classes were implemented different learning, then obtained the average value of class Five-A by using DRTA strategy that is 103.83 and the average value of class Five-B by using conventional learning is 96.06. From the result of the average score of students' reading comprehension using DRTA strategy is higher than the average score of reading ability using conventional learning.Hypothesis test using Independent test formula between two factors produced result of data class posttest V-A and class V-B that is and because it can be concluded that students 'learning outcomes using the DRTA strategy have an influence on students' reading comprehension on Indonesian language subjects in grade Five of MIS Alkhairat Delitua Academic Year 2016/2017.